Skeletal manifestations of congenital syphilis: rare but clinically relevant - Pg Mohammad Nizam Pg Mohammad Hussein; Kew, Seih Teck; Nang Khin Mya; Fairrul Kadir; Teh, Yong Guang (Elsevier Inc., 2021)
Congenital syphilis occurs as a result of maternal transmission of treponema pallidum in utero. This condition is mainly diagnosed by treponemal and non–treponemal serologic tests. However, both maternal nontreponemal and treponemal IgG antibodies can be transferred through the placenta to the fetus, thus complicating its interpretation soon after birth. We report a case of a neonate with congenital syphilis whose mother became infected after the first trimester of pregnancy. We report how skeletal radiographs expedite the clinical decision-making process and direct further management of neonates. This case also highlights the need for repeated syphilis screening in the latter part of pregnancy.